Parasites of four ornamental fish from the Chumucuí River (Bragança, Pará, Brazil) - Fujimoto,Rodrigo Yudi (2013)
The objective of the present study was to evaluate the parasite fauna of four species of ornamental fish collected in the Chumucuí River, municipality of Bragança, Pará, Brazil. From June 2006 to December 2007. Fishes (n=307) belonging to four species were collected, including 23 specimens of Moenkhausia sanctaefilomenae (redeye tetra), 37Carnegiella strigata (marbled hatchetfish), 7Chilodus punctatus (spotted headstander), and 240Astyanax bimaculatus (twospot astyanax). The parasites found belonged to three taxa: monogeneans in the gills, nematodes (larvae ofCapillaria sp. and Contracaecum sp.) in the digestive tract and liver and acanthocephalans (Quadrigyrus torquatus, Q. brasiliensis and Q. nickoli) in the stomach and intestine. Astyanax bimaculatus presented higher prevalence of acanthocephalans in the wet season, and lower prevalence of nematodes in the dry season. The possible importance of these parasites in the exportation of ornamental fish is discussed.